A Low Pass Filter With sub-Hz Cutoff Frequencies for a Portable On-Chip Lock-in Microinstrument - Pérez Bailón, Jorge; Calvo, Belén; Medrano, Nicolás (Jornada de Jóvenes Investigadores del I3A, 2018)
This paper presents a first-order single-ended fully-integrated Low Pass Filter (LPF) tunable from 114 mHz to 2.5 kHz, designed to conform the output stage of a portable lock-in amplifier requiring fc = 0.5 Hz, 5 Hz cutoff frequencies. It achieves the two target fc over a -40 to 120 °C range with a power consumption of 2.7 μW at 1.8 V supply, compact size and dynamic range above 80 dB.